ICRF resonance cones in the low-density scrape-off-layer of ASDEX Upgrade - Felix Paulus; Volodymyr Bobkov; Helmut Faugel; Helmut Fünfgelder; Oleksii Girka; Gustavo Grenfell; Roman Ochoukov; Wouter Tierens; Hartmut Zohm; the ASDEX Upgrade Team (Nuclear Fusion)
The ICRF slow wave is a potential carrier for parallel RF electric fields known to cause unwanted plasma-wall interactions in magnetic confinement fusion experiments. In nowadays machines the slow wave is usually confined to the far scrape-off layer or the limiter shadow, but conditions in future experiments and reactors may allow the slow wave to be propagative in a larger region. Simulations with RAPLICASOL for various geometries show that the ICRF slow waves appear as the so-called resonance cones (RCs) characterized by large localized electric fields. The RCs emerge from the points along the plasma-antenna interface where (in the cold plasma approximation) the radio frequency electric field diverges. We demonstrate that in the parameter range of interest, the propagation of the RCs in a plasma with a density gradient is defined by a simple geometric model, using the local plasma density and the frequency as input parameters. In the context of experiments at ASDEX Upgrade, simulations illustrate that the RCs can emerge from a single tile of the ICRF antenna limiter. Experiments at the Ion-cyclotron System Hardware Test ARrangement (ISHTAR) were conducted to test the detection principle in a simple environment. In agreement with simulations and with predicted characteristics which depend on operation parameters, the RCs are excited by an RF antenna and propagate through the relatively homogeneous plasma in ISHTAR. The cones are detected at a distance from the antenna using two probes scanning through the plasma. In ASDEX Upgrade, a single tile of an antenna limiter was modified to launch RF power into a specially tailored low-density scrape-off layer. Probes at the mid-plane manipulator were then used to detect the wave electric fields at a distance from the RF source. The detected RF signals show that the signal maxima are located close to the lower hybrid resonance density and are highest when the source and the probes are connected along magnetic field lines. These observations agrees with the model for RCs from the simulations.